THE STUDY OF BIOMASS HUMIDITY IMPACT ON THE EFFICIENCY OF A POWER GENERATING SYSTEM WITHA GASIFIER AND THE STIRLING ENGINE - Anisimov, Pavel Nikolaevich; Onuchin, Evgenij Mikhajlovich; Vishnevskaya, Maria Mikhajlovna; Sidyganov, Jurij Nikolaevich; Medjakov, Andrej Andreevich (Journal of Applied Engineering Science, 2016)
The aim of this study is to determine the impact of fuel wood chips humidity on the overall efficiency of the power module mobile chipper consisting of a gasifier, the Stirling engine and a container-dryer, as well, as to research utilization efficiency of heat emissionsof the Stirlingengine in a container-dryer of self-design. A mathematical model of the autonomous power module mobile chipper with fuel chips functioning was created. In addition, the physical experiment was conducted to determine the actual moisture content of wood chips after drying due to thermal emissions of the Stirling engine. According to the results of the experiments we obtained regression equations of the efficiency of the power-generating unitdependence on the initial moisture content of biofuels for two cases - with drying in the container-dryer and without drying. Drying of fire wood chips due to utilization of thermal emissions of the Stirling engine in a container-drier of a proposed design improves the efficiency of the power-generating unit. The reduction of the fuel wood relative humidity from 47.5% to 37.5% increases the efficiency by 7.34%,while moisture reduction from 37.5% to 27.5% results in higher efficiency of only 4.37%, a further reduction in moisture from 27.5% to 17.5% results in higher efficiency of only 2.47%. Thus, the greatest positive effect of drying fire wood chips due to heat recovery of the Stirling engine emissions is observed when using fuel wood with high initial moisture content of more than 30%.